Low digestive hemorrhage caused by a vascular malformation in a patient with Crohn's disease: case report and literature review - Santos, Carlos Henrique Marques dos; Stefanello, José Valério Librelotto, II; Carvalho, Yuri Maciel; Senefonte, Flávio Renato de Almeida (Journal of Coloproctology, 2016)
The authors report the case of a 19-year-old male patient with Crohn's disease treated with infliximab and azathioprine, with sustained clinical remission; in the course of the evolution, this patient showed a vascular malformation in his rectum, with daily massive bleeding, in need of several blood transfusions and finally with an indication for surgical treatment. Data from the literature on the association of the injury at issue and CD, as well as the drugs used by the patient, are evaluated. The literature lacks information linking this malformation with CD or with the drugs used.
Keywords: Crohn's disease; Complications; Vascular malformation